(untitled) (Journal of actual problems of jurisprudence, 2019)
In given article some questions of legal maintenance of participation of Republic Kazakhstan in foreign trade activities and the international economic relations are considered. The author analyzes problems of interaction of norms of the international and national right, main principles of the international cooperation.